Exploring ozone pollution in Chengdu, southwestern China: A case study from radical chemistry to O3-VOC-NOx sensitivity - Tan, Z. F.; Lu, K. D.; Jiang, M. Q.; Su, R.; Dong, H. B.; L.M. Zeng; Xie, S. D.; Tan,QW; Zhang, Y. H. (Science of the Total Environment, 2018)
We present the in-situ measurements in Chengdu, a major city in south west of China, in September 2016. The concentrations of ozone and its precursor were measured at four sites. Although the campaign was conducted in early autumn, up to 100 ppbv (parts per billion by volume) daily maximum ozone was often observed at all sites. The observed ozone concentrations showed good agreement at all sites, which implied that ozone pollution is a regional issue in Chengdu. To better understand the ozone formation in Chengdu, an observation based model is used in this study to calculate the ROx radical concentrations (ROx = OH + HO2 + RO2) and ozone production rate (P(O3)). The model predicts OH daily maximum is in the range of 4–8 × 106 molecules cm−3 , and HO2 and RO2 are in the range of 3–6 × 108 molecules cm−3 . The modelled radical concentrations show a distinct difference between ozone pollution and attainment period. The relative incremental reactivity (RIR) results demonstrate that anthropogenic VOCs reduction is the most efficient way to mitigate ozone pollution at all sites, of which alkenes dominate >50% of the ozone production. Empirical kinetic modelling approach shows that three out of four sites are under the VOC-limited regime, while Pengzhou is in a transition regime due to the local petrochemical industry. The ozone budget analysis showed that the local ozone production driven by the photochemical process is important to the accumulation of ozone concentrations.